Analisis Faktor-Faktor Kinerja Keuangan Perusahaan - Kurniawati, Yeni; Hendri, Nedi; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to determine the financial performance of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018–2021 period. The type of research used is qualitative analysis and uses descriptive research techniques. Data collection uses secondary data obtained from audited financial reports. The population and sample used purposive sampling, with a sample size of 20 companies. The results of the study can be concluded to show that the capital structure as measured by the debt-to-equity ratio (DER) and leverage as measured by the debt-to-asset ratio (DAR) are fairly good financial performers. Meanwhile, sales growth for financial performance is less good or less efficient.